EVALUASI PENERAPAN SANITASI ALAT TERHADAP KEAMANAN PANGAN PADA INDUSTRI KERIPIK TEMPE SUKA NICKY BANJARNEGARA - , INDRIYANI IDA SUPRAPTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sanitation is an effort to reduce the number of microbes that exist to achieve food safety. The equipment in the food industry should be considered the sanitation because it deals directly with the raw materials that will affect the products. The observation was did on tempe chips industry \"Suka Nicky\" in Banjarnegara on July-August 2013 by comparing the real application of sanitation in the industry with regulation published by âKepala Badan POM tentang Cara Produksi Pangan yang Baik Tahun 2012â. The industry does 93.05% of the regulation mentioned above. Meanwhile, the 6.95% is categorized to be inappropriate regarding to regulation. Still there are irregularities in the use of equipment that are made from bamboo, as well as the facility for sanitation, that is the usage of dumpster.